2022
DOI: 10.1155/2022/9661940
|View full text |Cite
|
Sign up to set email alerts
|

The mir-21 Inhibition Enhanced HUVEC Cellular Viability during Hypoxia-Reoxygenation Injury by Regulating PDCD4

Abstract: The purpose of this study was to explore the clinical value of altered plasma mir-21 expression level as a biomarker for the severity of coronary artery disease (CAD) and its molecular impact on HUVEC cellular injuries. Angiographically validated 56 patients with single-vessel CAD disease, 92 patients with double-vessel CAD, 139 complex coronary artery stenosis patients, and 56 healthy individuals ( n = 343 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several authors already indicated the role of miR-21 as an inflammation marker in age-associated diseases [20,21] which was characterized by a prominent activation of the innate immune response. Besides elevated circulatory miR-21 concentrations have a positive correlation with aging [2]. Our group have reported that miR-21 was abundant in extracellular vesicles from aging-MSC and after conducting functional experiments inhibiting its expression, it was demonstrated the link between miR-21 expression and damage-associated molecular patterns and SASP by aging [9].…”
Section: Discussionmentioning
confidence: 89%
“…Several authors already indicated the role of miR-21 as an inflammation marker in age-associated diseases [20,21] which was characterized by a prominent activation of the innate immune response. Besides elevated circulatory miR-21 concentrations have a positive correlation with aging [2]. Our group have reported that miR-21 was abundant in extracellular vesicles from aging-MSC and after conducting functional experiments inhibiting its expression, it was demonstrated the link between miR-21 expression and damage-associated molecular patterns and SASP by aging [9].…”
Section: Discussionmentioning
confidence: 89%
“…In a rat model of drug-induced cardiac injury, miR-21 was specifically localized to inflammatory cell infiltrates in the heart and therefore was suggested as a biomarker of cardiotoxicity [47]. In patients with coronary heart disease, expression of plasma miR-21 was found to be progressively higher in single-, dual-, and multivessel occluded coronary artery disease patients [14]. In heart failure patients, the level of plasma miR-21 was higher than in healthy controls, but no association between this miRNA and the prognostic outcome parameters was described [48].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with coronary artery disease, the expression of miR-21 in plasma samples progressively increased in those with single-, dual-and multivessel occlusion. This suggests the potential diagnostic capability of miRNAs for cardiac damage [14]. Furthermore, multiple studies have focused on the identification of biomarker miRNAs in small extracellular vesicles (EVs) or exosomes in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…As a cancer-inhibiting protein, PDCD4 is involved in the occurrence and development of tumors [10] . Recent years, numerous studies have reported the role of PDCD4 in other diseases such as polycystic ovary syndrome, obesity, diabetes, and coronary artery atherosclerosis [11][12][13][14] . PDCD4 also plays a crucial regulatory role in in ammation [15] .…”
Section: Introductionmentioning
confidence: 99%